The asset allocation of defined benefit pension plans: the role of sponsor contributions - Artem Dyachenko; Patrick Ley; Marc Oliver Rieger; Alexander F. Wagner (Journal of Asset Management, 2022)
What percentage of its assets should a defined benefit pension plan invest into stocks as its funding ratio varies? We show that the answer to this question depends on the institutional setting and in particular on the extent to which the sponsoring company contributes to the fund as the funding ratio varies. We consider two settings: in one setting, the sponsoring company contributes to its pension fund only if the funding ratio is below the target level (as is the case, for example, in the US); in the other setting, the sponsoring company always contributes to its pension fund (as is the case, for example, in Switzerland). We show that these two institutional frameworks lead to two different dynamics, conditional distributions of the funding ratios, and relationships between the current funding ratio and investment into stocks. For settings like the US, that relation is non-monotonic while for settings like in Switzerland, it is monotonically decreasing. Previous empirical findings point towards a similar pattern.
Keywords: 330; Pension funds; Asset allocation; Dynamic optimization